Riscos ocupacionais do bombeiro militar: uma proposta de modelo de estratégias protocolares padronizadas de gerenciamento durante e após ações de combate a incêndios - Oliveira, Renan Augusto Bortolassi de (2022)
Military firefighters are regularly exposed to various occupational hazards inherent in their work activity, during fire fighting, rescue at height, rescue and vehicular rescue, emergencies with dangerous products, among others. The Paraná Fire Department attended, from 2018 to 2021, approximately 81,000 occurrences involving fires, with an average of 20,000 events per year and at least 50 daily occurrences that are attended by 148 Fire Department stations in the State of Paraná. Currently, an approximation PPE is used to attend to this type of occurrence involving fires. The present research intends to evaluate the physical condition (vital signs) of the Firefighter who is facing adverse conditions controlled in a real-time container-type firefighting simulator (CFBT) in order to identify the problems caused to the health of the military firefighter due to of the use of personal protective equipment for fire fighting and respiratory protection equipment, during emergency care, in addition to evaluating the degree of exposure to which this professional is subjected and the occupational risks involved in order to propose a procedure for the improvement of the physical capacity of firefighters in this activity. Providing a better service to the occurrence and mainly increasing the safety of the firefighters involved. With the identification of occupational risks, a standard operating procedure will be presented, aiming to reduce the exposure of firefighters, through the establishment of protocols for periods of work and rest, including rehabilitation procedures (self-rehabilitation or formal rehabilitation), so that they can return activity, always prioritizing the occupational health of these public safety professionals. The method used was developed from the measurement of heart rate variability, blood pressure, body temperature of a group of military firefighters, during instruction in CFBT. 16 Firefighters from Coci 2021 performed two working conditions, one with 30 minutes of uninterrupted exposure (activity X), and the other, with 15 minutes of exposure, 10 minutes of rest, followed by another 15 minutes of exposure (activity Y). The measurements took place before, during and after exposure to the simulator. Statistical analysis was performed using the 20th version of the Statistical Package for the Social Sciences software (SPSS v20). The results showed that there were significant variations in the time item (before and post-activity), but there were no significant variations between the X and Y conditions. In addition to presenting values that demonstrated an accumulated wear of the sample in the before-activity measurements. The conclusion of the work was the presentation, to the command of the Fire Department of the Military Police of the State of Paraná, of a standardized operational protocol - POP -, exposing a work routine of 30 minutes of work with 10 minutes of self-rehabilitation.